Early non‐invasive selection of patients at high risk of severe hepatitis C recurrence after liver transplantation. Issue 3 (30th May 2016) - Crespo, G.; Gambato, M.; Millán, O.; Casals, G.; Ruiz, P.; Londoño, M.C.; Mira, A.; Forns, X.; Brunet, M.; Jiménez, W.; Navasa, M.
Abstract: Background: The early identification of patients at high risk of severe post liver transplant hepatitis C recurrence is relevant, as these patients may be treated using interferon (IFN)‐free regimens. Methods: In a retrospective study with prospectively collected data, we investigated whether the use of several non‐invasive methods (fibrosis 4 index [FIB‐4], AST‐to‐platelets ratio index [APRI], enhanced liver fibrosis test [ELF], IFN‐γ‐inducible protein 10 [IP‐10], and transient elastography by Fibroscan) and their combinations 6 months after transplantation could identify those recipients at higher risk of severe recurrence, defined by the presence of significant fibrosis (F ≥2) and/or portal hypertension (hepatic venous pressure gradient ≥6 mmHg) 12 months after transplant. Seventy‐two hepatitis C virus (HCV)‐infected liver transplant patients and 10 recipients in whom HCV was eradicated before transplantation were included in the study. Results: The levels of all biomarkers were significantly higher in HCV‐infected recipients than in controls. Among HCV recipients, levels of biomarkers were significantly higher in patients with severe recurrence. Although there were no statistically significant differences between biomarkers, APRI, ELF, and FIB‐4 obtained the highest area under the ROC curve values. The combination of serum biomarkers with Fibroscan increased the negative and positive predictive values, although diagnostic accuracy of individual tests was not significantly improved. Conclusions: Patients at higher risk of severe HCV recurrence can be identified early, 6 months after transplantation, using readily available non‐invasive methods.